Supporting Wildfire Response During a Pandemic in the United States: the COVID-19 Incident Risk Assessment Tool - Thompson, Matthew P.; Belval, Erin J.; Dilliott, Jake; Bayham, Jude (Frontiers in Forests and Global Change, 2021)
The onset of the global pandemic in 2020 significantly increased the complexity and uncertainty of wildfire incident response in the United States, and there was a clear role for decision support to inform and enhance coordination and communication efforts. Epidemiological modeling suggested the risk of COVID-19 outbreak at a traditional large fire camp could be substantial and supported the broadscale implementation of mitigations, and management of COVID-19 required expanding the response network to interface with entities such as local public health agencies, hospitals, and emergency operations centers. Despite the early issuance of medical and public health guidance to support wildfire management functions under a COVID-19 modified operating posture, an identified gap was a scale- and scope-appropriate tool to support incident-level assessment of COVID-19 risk. Here we review the development and application of a COVID-19 Incident Risk Assessment Tool intended to fill that gap. After prototyping with fire managers and risk practitioners, including early-season use on several incidents, we built an online dashboard that was used operationally throughout the 2020 fire season. We summarize usage statistics, provide some examples of real use on wildfire incidents, and report feedback from users. The tool helped to fill a critical information gap and was intended to support risk-informed decision-making regarding incident logistics, operations, and COVID-19 mitigations.